Faktor Pengaruh dalam Pembentukan Permukiman Kumuh di Desa Pohuwato Timur - Fendy Faizal Gobel; Eko Adityawan T. Zees (Universitas Sebelas Maret Surakarta, 2022)
Pohuwato Timur Village is included in several slum areas in Pohuwato District. Most of the residents' houses in this area have low building quality, high building density, narrow road space, poor condition of drainage channels, and accumulation and pollution of river waste. The society also has unhealthy behavior by disposing their solid waste in the river and by using the embankment as the toilet. This research aims at investigating the condition of slums and the factors that influence the creation of slums. The results of the identification and analysis are used as guidelines in making directions for handling regional structuring. Identification of slum conditions is carried out on five indicators. The research method applies a quantitative approach and multiple linear regression analysis. Data collection techniques are questionnaires and observations. The identification results show that in general, it is a medium slum area. The results of the analysis show that residential buildings, environmental roads, drainage channels, wastewater disposal, and solid waste management simultaneously affect the slum conditions of the area, while partially only drainage and waste channels affect the slum conditions of the area. The direction of the arrangement is carried out with a pattern of handling resettlement with the principle of On-site Reblocking arrangement, as well as repair and arrangement of facilities and infrastructure of drainage and waste channels.